Green Chemistry 2018
DOI: 10.5772/intechopen.70419
|View full text |Cite
|
Sign up to set email alerts
|

Green Chemistry and Synthesis of Anticancer Molecule

Abstract: Green chemistry is a modern area of chemistry merged with chemical engineering methods. It highlighted the synthesis of molecules in a manner of using environment-friendly chemical reagents with low waste material for enhancing environmental performance which reduce the formation of hazard substances. Modern researches are trying to reduce the risk of human kind health and the environment of our world by doing magnificent work in the field of green chemistry. In the pharmaceutical field, green chemistry works … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Nanomaterials are much more efficient than chemotherapeutics in delivery to the target site . However, further research is being conducted to improve the penetration of large sized NPs through introducing cross-linking methods. Ju et al reported the formulation of a nanogel containing a polyelectrolyte core cross-linkage comprised of N -lysinal- N ′-succinyl chitosan and poly­( N -isopropylacrylamide) along with a cross-linked shell of bovine serum albumin which showed swelling in an acidic environment followed by shrinking under neutral conditions . This swelling was responsible for quickly releasing the encapsulated chemotherapeutic agent into the cancer cells for effective cytotoxicity.…”
Section: Characterization and Synthesis Of Biopolymeric Nps Used In D...mentioning
confidence: 99%
“…Nanomaterials are much more efficient than chemotherapeutics in delivery to the target site . However, further research is being conducted to improve the penetration of large sized NPs through introducing cross-linking methods. Ju et al reported the formulation of a nanogel containing a polyelectrolyte core cross-linkage comprised of N -lysinal- N ′-succinyl chitosan and poly­( N -isopropylacrylamide) along with a cross-linked shell of bovine serum albumin which showed swelling in an acidic environment followed by shrinking under neutral conditions . This swelling was responsible for quickly releasing the encapsulated chemotherapeutic agent into the cancer cells for effective cytotoxicity.…”
Section: Characterization and Synthesis Of Biopolymeric Nps Used In D...mentioning
confidence: 99%
“…From all the approaches of NPs synthesis, green synthesis approach is considered the most economic, sustainable, reliable and eco-friendly [ 37 ]. This approach of NPs synthesis does not require toxic chemicals, high temperature, high pressure and does not cause harm to human health and the environment [ 38 ].…”
Section: Green Synthesized Metallic Nps: An Insightmentioning
confidence: 99%
“…In the biopharma sector, unlike the traditional pharmaceutical industry, green chemistry focuses on the design of facile, eco-friendly, cost-efficient, sustainable, and high yielding methods for the synthesis of new drugs that are safe for human health and environment. For the synthesis of anticancer molecules, for example, green methods were developed based on physicochemical procedures as microwave irradiation, ultrasonic irradiation, Claisen-Schmidt condensation, green solvents, and high temperatures (from 80 to 130 • C) to obtain product yields of 70% and 96% [28]. However, the green physicochemical procedures still require special equipment, multiple chemicals consumption, and large quantities of energy.…”
Section: Laccases For Pharmaceutical Green Chemistrymentioning
confidence: 99%